Retrograde signaling in plants: from simple to complex scenarios - Leister, Dario (Frontiers in Plant Science, 2012)
The concept of retrograde signalling posits that signals originating from chloroplasts or mitochondria modulate the expression of nuclear genes. A popular scenario assumes that signalling factors are generated in, and exported from the organelles, then traverse the cytosol, and act in the nucleus. In this scenario, which is probably over-simplistic, it is tacitly assumed that the signal is transferred by passive diffusion and consequently that changes in nuclear gene expression (NGE) directly reflect changes in the total cellular abundance of putative retrograde signalling factors. Here, this notion is critically discussed, in particular in light of an alternative scenario in which a signalling factor is actively exported from the organelle. In this scenario, NGE can be altered without altering the total concentration of the signalling molecule in the cell as a whole. Moreover, the active transport scenario would include an additional level of complexity, because the rate of the export of the signalling molecule has to be controlled by another signal, which might be considered as the real retrograde signal. Additional alternative scenarios for retrograde signalling pathways are presented, in which the signalling molecules generated in the organelle and the factors that trigger NGE are not necessarily identical. Finally, the diverse consequences of signal integration within the organelle or at the level of NGE are discussed. Overall, regulation of NGE at the nuclear level by independent retrograde signals appears to allow for more complex regulation of NGE than signal integration within the organelle.